Pharmacoeconomics of sublingual immunotherapy with the 5-grass pollen tablets for seasonal allergic rhinitis - Lombardi, Carlo (Clin Mol Allergy, 2017)
Allergic rhinitis has a very high burden regarding both direct and indirect costs. This makes essential in the management of AR to reduce the clinical severity of the disease and thus to lessen its costs. This particularly concerns allergen immunotherapy (AIT), that, based on its immunological action on the causes of allergy, extends its benefit also after discontinuation of the treatment. From the pharmacoeconomic point of view, any treatment must be evaluated according to its cost-effectiveness, that is, the ratio between the cost of the intervention and its effect. A favorable cost-benefit ratio for AIT was defined, starting from the first studies in the 1990s on subcutaneous immunotherapy (SCIT) in AR patients, that highlighted a clear advantage on costs over the treatment with symptomatic drugs. Such outcome was confirmed also for sublingual immunotherapy (SLIT), that has also the advantage on SCIT to be free of the cost of the injections. Here we review the available literature on pharmacoeconomic data for SLIT with the 5-grass pollen tablets.